Characterisation of the genetic diversity of East African cattle breeds using microsatellite DNA markers. - Okomo, M.A. (University of Nairobi, 1998)
The indigenous cattle populations of Eastern Africa are vital tr the subsistence and economic development of the region, providing essential food products, sustaining the employment and income of millions of East Africans living in the rural areas, and providing manure as well as draft power used in ploughing and transport. In comparison to their exotic counterparts, these cattle are better adapted to survive and reproduce under the region's harsh environments. They are currently at risk of extinction due to indiscriminate crossbreeding and replacement with exotic breeds, uncontrolled introgression and interbreeding, absence of breed development programmes and political instability, and immediate steps must be taken to conserve them. Despite their importance, these cattle have not been well defined, classified or studied adequately in the past. Their current classification based on historical and anthropological evidence, and phenotypic data is inaccurate, making implementation of rational conservation and utilisation strategies difficult. Their genetic characterization based on DNA polymorphism is more reliable and precise, and therefore necessary. This study' utilized 18 autosomal microsatellite markers and one Y-chromosome specific microsatellite marker, to characterize genetically, seven cattle populations indigenous to East Africa (Abigar, Danakil, Sheko, Arado, Kenyan Boran, Kavirondo Zebu and Kilimanjaro Zebu) and three reference breeds (Sahiwal, N'Dama and Friesian). A minimum of 35 animals were studied per breed. The microsatellite loci studied were highly polymorphic, with a total of 208 different alleles observed across the autosomal loci and two at the V-chromosome specific locus. There was significant variation in allele numbers and frequencies among the breeds. Withinbreed diversity was high in all breeds with expected heterozygosities ranging from 0.513 (N'Dama) to 0.710 (Kenyan Boran), and observed heterozygosities from 0.511 (N'Dama) to 0.660 (Friesian). All the populations except the Kenyan Boran were at Hardy-Weinberg equilibrium. Genetic distances were estimated between, breed pairs using two distance measures, Neis standard genetic distance (Dg) and the Nei et al., DA distance. The Ds distances ranged from 0.023 (Danakil and Abigar) to 0.868 (N'Dama and Sahiwal), and DA from 0.058 (Danakil and Kilimanjaro Zebu) to 0.462 (N'Dama and Sahiwal). Four phylogenetic trees were constructed to assess genetic relationships among breeds, using two tree construction methods (UPGMA and NJ) and the two genetic distances (Os and DA). A principle component analysis of allele frequencies was also done to complement the phylogenetic analysis. All the trees constructed and the principle components graph exhibited two major clusters. The first cluster contained the Friesian and N'Dama (pure Bas taurus from Europe and Africa, respectively), while the second contained the Sahiwal (pure Bas indicus) and all the East African cattle breeds studied. On the UPGMA trees and the principle components graph, within the second cluster, the Sahiwal was separated from the indigenous East African cattle breeds. All the different classes of indigenous East African cattle studied showed close genetic relationship. No clear genetic distinction was evident 'between the humped breeds (zebu and sanga) and the humpless taurine breed (Sheko), and therefore the current classification of these breeds based on morphology does not hold. Analysis of indicine- and taurine-specific (diagnostic) alleles, as well as Y-chromosomal DNA analysis revealed taurine influence in the East African zebu breeds, zebu introgression in the East African taurine, and a higher proportion of zebu background relative to taurine in the East African sanga breeds. These results indicated that the East African cattle studied contained both indicine and taurine backgrounds and were therefore homogenous and unique, hence there is no genetic justification, only phenotypic, in separating them into different categories.